Knowledge, compensation, and firm value: An empirical analysis of firm communication - Li, Feng; Minnis, Michael; Nagar, Venky; Rajan, Madhav (Journal of Accounting and Economics, 2014)
Knowledge is central to managing an organization, but its presence in employees is difficult to measure directly. We hypothesize that external communication patterns reveal the location of knowledge within the management team. Using a large database of firm conference call transcripts, we find that CEOs speak less in settings where they are likely to be relatively less knowledgeable. CEOs who speak more are also paid more, and firms whose CEO pay is not commensurate with CEO speaking have a lower industry-adjusted Tobin׳s Q. Communication thus appears to reveal knowledge.